PENGARUH WAKTU PENCUCIAN TERHADAP SIFAT MEKANIS PRODUK LATEKS KARET ALAM RENDAH PROTEIN - - Yuniati; - Adriana; Ramzi Jalal (Jurnal Teknologi, 2014)
This study is aimed to observe the use of coconut shell  used as Carbon  for  filler material for  gloves making. Two important factors in making  gloves with the immersion technique  are  leaching and heating processes   that can increase the mechanical properties. This research is also aimed to find a solution of washing procedure  and the best time  to get the mechanical properties, so  the laundering can  reduce the  allergic reaction for the sentive users... A method which has been experienced is  maturation process  for 24 hours and was condunted of vulcanization by  drying it in the oven with  100 °C for 15 minutes. The leaching process of the film is conducted by using some sort of solutions ;  aquadest, 1% sodium hydroxide and 1% Ammonium hydroxide . The examining time used for laundering and soaking are 30, 60 and 90 minutes.. The highest tensile strength was obtained in 30 minutes soaking time with 25,3 MPa Aquadest. . The tensile strength increased along with the extra time for laudering and soaking process in 90 minutes with aqudest and 90 minutes with 800 % sodium hydroxide. . The highest modulus , 300 %, was obtained in 90 minutes soaking/ laundering time in 1,7 Mpa Ammonium Hydroxide solution